Relicts of Paleoproterozoic LIPs in the Belomorian province, eastern Fennoscandian Shield: barcode reconstruction for a deeply eroded collisional orogen - Alexandra Stepanova (6743843); Vladimir S. Stepanov (11052506); Alexander N. Larionov (11052509); Ekaterina B. Salnikova (11052512); Alexander V. Samsonov (11052515); Pavel Azimov (11052518); Svetlana V. Egorova (11052521); Irina I. Babarina (11052524); Yulia O. Larionova (11052527); Maria A. Sukhanova (11052530); Anna V. Kervinen (11052533); Oleg A. Marksimov (11052536) (2021)
Table S1. Data on chemical composition of Paleoproterozoic mafic dykes and 20 intrusions in the Belomorian Province